Methylene blue vital staining for Trypanosoma cruzi trypomastigotes and epimastigotes Coloração vital com azul de metileno aplicada a tripomastigotas e epimastigotas de Trypanosoma cruzi - Cláudio S. Ferreira; Rita C. Bezerra; Ariadne A. Pinheiro (Revista do Instituto de Medicina Tropical de São Paulo, 2006)
The morphological identification of Trypanosoma cruzi is currently considered to have a high specificity, but its sensitivity, which depends on the volume of the sample examined, is rather low. Trypanosome developmental stages suspended in blood, reduviid feces, and culture media are routinely searched for by means of fresh film examination (about 2 µL). High speed centrifugation of blood samples separates the buffy coat, where most trypomastigotes concentrate. As the parasites are transparent and colorless, their detection is mostly dependent on their motility. The fluorescent vital stain acridine orange has been used to enhance image contrast, as exemplified by the QBC (Quantitative Buffy Coat) technique. Staining blood, buffy coat, reduviid feces, and culture media samples with methylene blue (also a vital dye) is a means of producing sharp, well contrasted images of motile or non-motile T. cruzi developmental stages, only standard laboratory microscopes being required. Slides previously coated with a thin layer of methylene blue are used to stain fresh blood films. Photomicrographs exemplify the results of methylene blue staining applied to living and fixed parasites. A identificação morfológica de Trypanosoma cruzi tem alta especificidade, segundo é geralmente aceito; entretanto, sua sensibilidade, dependente do volume da amostra examinada, é baixa. Formas evolutivas de T. cruzi suspensas em sangue, fezes de reduviídeos e meios de cultura são rotineiramente pesquisadas em esfregaços a fresco (cerca de 2 µL). Centrifugação de amostras de sangue a altas velocidades produz a separação do creme leucocitário, onde se concentram as formas tripomastigotas. Em preparações a fresco, a motilidade das formas tripomastigotas e epimastigotas de T. cruzi, protozoário transparente e incolor, facilita sua detecção. Laranja de acridina, corante vital fluorescente, tem sido usada para acentuar o contraste das imagens de parasitas. Disto é exemplo a técnica QBC (Quantitative Buffy Coat). A coloração por meio de azul de ...